1995
DOI: 10.1002/art.1780380710
|View full text |Cite
|
Sign up to set email alerts
|

High level of interleukin‐10 production by the activated t cell population within the rheumatoid synovial membrane

Abstract: Objective. To characterize the cytokine profile of the activated T cell population derived from the synovial membrane of rheumatoid arthritis (RA) patients. Methods. Interleukin‐2 (IL‐2) was used to select for in vivo–activated T cells from the synovial membrane of 2 patients with RA, and the cells were cloned nonspecifically. The cytokine production profile of these clones was compared with that of clones derived from peripheral blood monocytes (PBM) by stimulating all clones for 24 hours with immobilized ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
68
0
2

Year Published

1996
1996
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(71 citation statements)
references
References 12 publications
1
68
0
2
Order By: Relevance
“…Our demonstration that this allele results in higher levels of IL-10 production, which could thereby act to suppress the antineoplastic immune response, supports the negative impact of this polymorphism in NHL. Serum levels and ex vivo studies of monocytes and B cells from patients with SLE and rheumatoid arthritis have shown increased levels of IL-10 production (57,58). Several genetic studies have confirmed that the Ϫ571 polymorphism is overexpressed in populations of patients with SLE (52,59).…”
Section: Discussionmentioning
confidence: 99%
“…Our demonstration that this allele results in higher levels of IL-10 production, which could thereby act to suppress the antineoplastic immune response, supports the negative impact of this polymorphism in NHL. Serum levels and ex vivo studies of monocytes and B cells from patients with SLE and rheumatoid arthritis have shown increased levels of IL-10 production (57,58). Several genetic studies have confirmed that the Ϫ571 polymorphism is overexpressed in populations of patients with SLE (52,59).…”
Section: Discussionmentioning
confidence: 99%
“…Unstimulated CD4 ϩ T cells from synovial fluid produce large quantities of IL-4 and IL-10 and deficient levels of interferon-␥ and IL-2 [30]. In addition, synovial tissue lymphocytes produce significant quantities of IL-10 [31]. The diverse nature of the immune response in rheumatoid arthritis may reflect the complex immunoregulatory networks that are evident in human disease.…”
Section: The Role Of Il-4 Il-10 and Interferon-␥ In The Reactivatiomentioning
confidence: 99%
“…Further to this, IL-10 is also abundantly expressed in the rheumatoid synovium (5), and it has been demonstrated that T cell clones from RA synovium produce higher levels of IL-10 than T cell clones derived from peripheral blood (6).…”
mentioning
confidence: 93%